Effect of Brand Image and Price Towards Purchase Intention In Beef-Jerky Company - Kwandy, C. P. (Review of Management and Entrepreneurship, 2017)
Royale Meat is a beef-jerky company established in March 2013. Recently the company has encountered problem related with the decline of sales transaction, hence this study will address this particular problem by analyzing the influence of brand image and pricing strategy towards purchasing intention. Sample for this research is Royale Meat customer, 67 questionnaires were distributed using both online and offline questionnaires. Regression Analysis was used to analyze the effect. Result findings from this research show that brand image and price both have significant effects on purchase intention. Correlation Coefficient R value shows strong relation of 0.85and Coefficient of determination shows 0.722 describing the ability to explain factors influencing purchase intention is 72.2%. This study has confirmed that both independent variables are strong predictors for purchase intention.